Ensiklopedia : Adaptasi Struktural Dan Fungsional Organ Reproduktif Pada Tumbuhan Di Lingkungan Ekstrem (International Forum of Researchers and Lecturers, 2024)
Plants living in extreme environments have developed significant adaptations in their reproductive organs to survive and reproduce. These adaptations include structural and functional changes in reproductive organs to overcome harsh environmental challenges such as drought, extreme temperatures, and infertile soil conditions. Examples of these adaptations include cacti with spiny stems and drought-resistant flowers, Arctic willows with their fast flowering times, and pine trees with their vigorous growth and efficient pollen cones. This research explores the mechanisms of plant adaptation in extreme environments, discusses the implications for plant survival and reproduction, and identifies structural and functional changes in reproductive organs in response to environmental stress.